Development and testing of anode-supported solid oxide fuel cells with slurry-coated electrolyte and cathode - Muccillo, R.; Muccillo, E. N. S.; Fonseca, F. C.; Franca, Y. V.; Porfirio, T. C.; de Florio, D. Z.; Berton, M. A. C.; Garcia, C. M. (Elsevier B.V., 2006)
A laboratory setup was designed and put into operation for the development of solid oxide fuel cells (SOFCs). The whole project consisted of the preparation of the component materials: anode, cathode and electrolyte, and the buildup of a hydrogen leaking-free sample chamber with platinum leads and current collectors for measuring the electrochemical properties of single SOFCs. Several anode-supported single SOFCs of the type (ZrO(2):Y(2)O(3)+NiO) thick anode/(ZrO(2):Y(2)O(3)) thin electrolyte/(La(0.65)Sr(0.35)MnO(3)+ZrO(2):Y(2)O(3)) thin cathode have been prepared and tested at 700 and 800 degrees C after in situ H(2) anode reduction. The main results show that the slurry-coating method resulted in single-cells with good reproducibility and reasonable performance, suggesting that this method can be considered for fabrication of SOFCs. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: solid oxide fuel cells; solid electrolyte; anode; cathode; impedance spectroscopy